Strategi Pemasaran Dalam Meningkatkan Customer Relationship Pelanggan Skincare Super Beauty - Sifana Nahdalia; Heri Prabowo; Ika Indriasari (Journal of Management and Social Sciences, 2024)
Marketing strategy is an activity carried out by a company to increase sales by establishing good relationships with customers. Super Beauty's lack of interaction with customers has resulted in the products being marketed not being communicated clearly to consumers. This research uses a qualitative approach by collecting data through observation, interviews and documentation. The selection of research informants used a purposive sampling technique which was determined based on certain considerations. Based on the research results, it was concluded that: 1. Implementation of customer relations from company managers via WhatsApp Blast, Shopee live streaming, events (exhibitions), and the Web. Meanwhile, Super Beauty's marketing strategy utilizes price affordability, Affiliate, and member get member programs, 2. Factors driving the implementation of customer relations include: price affordability, and high demand for skincare needs. 3. Factors inhibiting the implementation of customer relations include time constraints, low company budgets, and market demands. According to research results, the implementation of customer relations via WhatsApp blast from various social media is considered very effective. So, consumers feel moved to repurchase skincare products.